Pendidikan Berbasis Merdeka Belajar dalam Al-Qur’an - M. Agil Febrian; Siti Qamariah; Asnil Aidah Ritonga; Mohammad Al Farabi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The research that has been carried out is entitled "Education Based on Freedom of Learning". This research aims to find out the verses of the Koran related to independent learning-based education. This research uses a method. The research method used is the library research method, namely research carried out by utilizing literature (libraries) in the form of books, notes or reports of research results from previous research. After the data was analyzed, the results of the research showed that through verses 1-5 of Q.S al-'Alaq, Allah SWT sent down revelations to the Prophet Muhammad SAW to learn how to seek knowledge. Allah SWT recommends humans to read and write and carry out teaching and learning activities. Q.s Al-Jumuah:2 And the original meaning of the word (ummiy) is a person who cannot read and write; and most Arabs at that time could not read or write. Although the Prophet could not read or write, nor did he learn from anyone (purify them). Surah Al-Kahf: 28 explains that people are strong enough to restrain themselves from the shackles of lust. So we as educators and as students can overcome ourselves from the shackles of lust and can save students from lust